Local contagion and regional compression: habitat selection drives spatially explicit, multiscale dynamics of colonisation in experimental metacommunities. (22nd December 2015) - Resetarits, William J.; Silberbush, Alon
Abstract: Habitat selection, including oviposition site choice, is an important driver of community assembly in freshwater systems. Factors determining patch quality are assessed by many colonising organisms and affect colonisation rates, spatial distribution and community structure. For many species, the presence/absence of predators is the most important factor affecting female oviposition decisions. However, individual habitat patches exist in complex landscapes linked by processes of dispersal and colonisation, and spatial distribution of factors such as predators has potential effects beyond individual patches. Perceived patch quality and resulting colonisation rates depend both on risk conditions within a given patch and on spatial context. Here we experimentally confirm the role of one context‐dependent processes, spatial contagion, functioning at the local scale, and provide the first example of another context‐dependent process, habitat compression, functioning at the regional scale. Both processes affect colonisation rates and patterns of spatial distribution in naturally colonised experimental metacommunities.